(untitled) (Comprehensive Journal of Science, 2026)
This study examines the phenomenon of lovers’ emaciation in ancient Arabic poetry as an unconscious defense strategy, transcending traditional rhetorical readings. It employs psychological and descriptive-analytical approaches to deconstruct the architecture of "dual defense mechanisms" (the integration of two mechanisms) and "complex defense mechanisms" (three or more mechanisms) devised by the subconscious mind to protect the self from existential collapse. The research concludes by highlighting the poet’s ingenuity in employing these complex systems to transform physical deterioration from an organic weakness into an argumentative tool, thereby achieving an artistic immortality that triumphs within the realm of the text.